Jaundice and photosensitization in indigenous sheep of Malaysia grazing on Brachiaria decumbens - Othman, Abas Mazni; Yusuff, Mohd. Khusahry; Abdul Rahman, Sheikh Omar (Veterinary Association Malaysia, 1983)
Observations on twelve indigenous sheep grazed on pasture of Brachiaria decumbens in MARDI, Serdang was carried out. Within 44 days of grazing five animals died, all showing signs of jaundice and photoserisitization. All twelve animals showed significant reduction in body weight. There was also marked increase in SGOT (serum glutamate oxaloacetate transaminase) and total bilirubin with values ranging from 330-1891 U/I and 5.47-13.06 mg/100 ml respectively. Changes in haematological pictures (RBC, PCV, Hb and WBC) and plasma protein were also observed. On necropsy all five carcasses showed ulceration on the skin particularly around the eyelids, muzzle, both upper and lower lips, tips of ear and the vulva. They also showed varying degrees of jaundice. The liver was consistently slightly enlarged, firmer than normal and had pale mottling. Histopathology indicated centrilobular necrosis of the liver thus indicating that the jaundice was due to toxic damage. It was concluded that a Brachiaria or Brachiaria associated was the aetiological agent